ABDOMINAL MYOMECTOMY AND ITS MORBIDITY - Faiz, Shakeel Ahmed; Shabbir, Nosheena Akhtar; Sadiq, Muhammad Shakil (Pakistan Journal of Physiology, 2018)
Background: Abdominal myomectomy has classically been viewed as a procedure associated with high intra operative and postoperative morbidity. This study was designed to review the experience with abdominal myomectomy and to assess morbidity associated with the procedure. Methodology: This study was conducted at Azad Jammu & Kashmir Medical College, Muzaffarabad. The hospital records of 116 women who underwent abdominal myomectomies from January 2012 to December 2016 were reviewed retrospectively. Particular attention was paid to blood loss and the febrile conditions. Blood loss was reckoned from surgeons’ operative notes. It was calculated by subtracting total irrigation fluid used from the total amount of fluid in the suction, the suction container at the end of surgery, then adding the amount of blood on the sponges, determined by weight. Ethical approval for article was obtained from Hospital Ethical Committee. The data collected was analyzed using SPSS-17. Chi-square test was applied and p<0.05 was taken as statistically significant. Results: The mean estimated intraoperative blood loss was (320±25 ml). Three (2.6%) had an estimated blood loss >1,000 ml and 1 (0.9%) had estimated blood loss of >1,500 ml. Febrile morbidity occurred in 26 (22.5%) patients, wound infection in 6 (5.3%), haemorrhage in 3 (2.7%) patients, and postoperative antibiotics were used in 66 (56.9%) cases. There was no re-admission and no mortality associated with the procedure. Conclusion: Myomectomy may be an attractive alternative to hysterectomy in selected women with uterine leiomyomata, with an added advantage of preservation of women’s sexual and reproductive functions. Women with very large uterine size should not be denied this procedure for safety concerns. Keywords: Abdominal myomectomy, blood loss, transfusion, pyrexia, morbidity, mortality, women Pak J Physiol 2018;14(1):30–2